2016
DOI: 10.1111/bju.13500
|View full text |Cite
|
Sign up to set email alerts
|

Results of a randomized, double‐blind, active‐controlled clinical trial with propiverine extended release 30 mg in patients with overactive bladder

Abstract: ObjectiveTo compare the efficacy and safety of the 30 mg extended release (ER) formulation of propiverine hydrochloride with the 4 mg ER formulation of tolterodine tartrate in patients with overactive bladder (OAB) in a non-inferiority trial. Patients and MethodsEligible patients, aged 18-75 years and with symptoms of OAB, were enrolled in this multicentre, randomized, doubleblind, parallel-group, active-controlled study. After a 2-week screening period, patients were randomized at a 1:1 ratio to receive eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…37 In the study in which 324 patients using propiverine (30 mg/day) ER and tolterodine (4 mg/day) ER for 8 weeks, the improvement in symptoms was found to be 88.9% in the propiverine group and 77.8% in the tolterodine group, and the rate of discontinuation of treatment due to side effects is also reported to be lower in the propiverine slowrelease (ER 30 mg) group compared to tolterodine 4 mg ER group. 38 However, in different studies comparing propiverine (30 mg/day) and tolterodine ER (4 mg/day), the frequency of adverse events was observed to be comparable in both treatment groups (Figure 1). 34,40 In two studies comparing propiverine and oxybutynin, dry mouth and severe dry mouth were observed less frequently in the propiverine administration.…”
Section: Overview Of Literaturementioning
confidence: 91%
“…37 In the study in which 324 patients using propiverine (30 mg/day) ER and tolterodine (4 mg/day) ER for 8 weeks, the improvement in symptoms was found to be 88.9% in the propiverine group and 77.8% in the tolterodine group, and the rate of discontinuation of treatment due to side effects is also reported to be lower in the propiverine slowrelease (ER 30 mg) group compared to tolterodine 4 mg ER group. 38 However, in different studies comparing propiverine (30 mg/day) and tolterodine ER (4 mg/day), the frequency of adverse events was observed to be comparable in both treatment groups (Figure 1). 34,40 In two studies comparing propiverine and oxybutynin, dry mouth and severe dry mouth were observed less frequently in the propiverine administration.…”
Section: Overview Of Literaturementioning
confidence: 91%
“…Propiverinin klinik etkinliği 2 haftadan itibaren başlamakta olup 4. haftada optimum düzeye yükselmektedir. Son yapılan çalışmalarda uzun etkili propiverinin 8. haftada en yüksek klinik etkinliğe ulaştığı bildirilmiştir (25).…”
Section: Karma Etki Ile Elde Edilen Klinik Sonuçlarunclassified